The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/1365-2745.13381
|View full text |Cite
|
Sign up to set email alerts
|

Mycoheterotrophic plants living on arbuscular mycorrhizal fungi are generally enriched in 13C, 15N and 2H isotopes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…The MHP leaves’ 15 N patterns were found to be determined by the MHP’s root fungi (Schiebold et al 2017 ). Hitherto, 13 C and frequently 15 N enrichments of MHP with AM fungi were associated with fungal identity, different fungal communities and different geographic origin (Merckx et al 2010 ; Courty et al 2011 ; Giesemann et al 2020 ; Gomes et al 2020 ). The previous lack of proof of 13 C and 15 N enrichment of the AM fungus itself was a major point of limitation, which can now be addressed with the methods described here.…”
Section: Resultsmentioning
confidence: 99%
“…The MHP leaves’ 15 N patterns were found to be determined by the MHP’s root fungi (Schiebold et al 2017 ). Hitherto, 13 C and frequently 15 N enrichments of MHP with AM fungi were associated with fungal identity, different fungal communities and different geographic origin (Merckx et al 2010 ; Courty et al 2011 ; Giesemann et al 2020 ; Gomes et al 2020 ). The previous lack of proof of 13 C and 15 N enrichment of the AM fungus itself was a major point of limitation, which can now be addressed with the methods described here.…”
Section: Resultsmentioning
confidence: 99%
“…S2). Clamp bearing fungus Microscopic observation McLennan ( 1959 ) Stable isotopes Gomes et al ( 2020 ) G. similis Hymenochaetales Resinicium, Mycena, Gymnopus Molecular identification, stable isotopes Martos et al ( 2009 ) Resinicium is the most dominant. The Gymnopus sequence was nested within the Marasmiellus clade (Fig.…”
Section: Phylogeny and Evolution Of Sap-mhpsmentioning
confidence: 99%
“…The findings by Haselwandter and Read (1982) and our observation of 15 N enrichment are in agreement with the enzyme repertoire of DSE (Caldwell, Jumpponen, & Trappe, 2000) Simultaneously, the fertile stems of E. arvense turned out as most enriched in 13 C among all investigated plant samples. The enrichment in 13 C by the achlorophyllous fertile stems of E. arvense is in the typical range of 13 C enrichments found for fully mycoheterotrophic plants associated with AM fungi (Courty et al, 2011;Gomes et al, 2020;Merckx et al, 2010). Based on this 13 C enrichment found most pronounced for the achlorophyllous fertile stems of E. arvense and to a lower extent for all samples of chlorophyllous Equisetum species, we propose also an additional functional role of AM fungi for the here investigated Equisetaceae next to the function of DSE fungi-being aware of the fact that AM fungi were only sporadically found in our microscopic and molecular survey and that they are also only occasionally reported in the literature (Dhillion, 1993;Dickson et al, 2007;Fernández et al, 2008;Hodson et al, 2009;Koske et al, 1985).…”
Section: Discussionmentioning
confidence: 85%
“…Our suggestion of a partially mycoheterotrophic nutrition by chlorophyllous Equisetum species is supported by two other findings: (1) Significantly higher total N concentrations in all plant compartments in comparison to autotrophic reference plants. Increased total N concentrations are known as a wide-spread feature of many fully and partially mycoheterotrophic plants irrespective whether associated with fungi forming ECM (Gebauer & Meyer, 2003;Hynson et al, 2013;Stöckel, Meyer, & Gebauer, 2011) or AM (Gomes et al, 2020). 2 (Cormier, Werner, Leuenberger, & Kahmen, 2019;Cormier et al, 2018;Ziegler, 1994) and has been reported for fully, partially and initially mycoheterotrophic orchids, irrespective of whether associated with ECM or saprotrophic fungi of the rhizoctonia group (Gebauer et al, 2016;Schiebold, Bidartondo, Lenhard, Makiola, & Gebauer, 2018;Schweiger, Bidartondo, & Gebauer, 2018) as well as for fully and partially mycoheterotrophic plants associated with AM fungi (Giesemann, Rasmussen, et al, 2020;Gomes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation